An extension program for ACCase inhibitor resistance in Manitoba : A case study - Goodwin, M. (Phytoprotection, 1994)
An extension program designed to encourage farmers to adopt herbicide rotation in favor of continuous use of acetyl-CoA carboxylase inhibitor herbicides was launched in 1991. The program has led to high levels of awareness of herbicide rotation in Manitoba (> 90%). Adoption of herbicide rotation is estimated at approximately 40%, but producers who have started to rotate herbicides are assumed to be doing so on a limited "trial" basis.The use of this group of products continues at high levels due to a combination of producer preference for these chemicals and of reluctance to use alternatives.